2020
DOI: 10.1186/s12909-020-02115-3
|View full text |Cite
|
Sign up to set email alerts
|

An observational study of self-monitoring in ad hoc health care teams

Abstract: Background: Working in ad hoc teams in a health care environment is frequent but a challenging and complex undertaking. One way for teams to refine their teamwork could be through post-resuscitation reflection and debriefing. However, this would require that teams have insight into the quality of their teamwork. This study investigates (1) the accuracy of the self-monitoring of ad hoc resuscitation teams and their leaders relative to external observations of their teamwork and (2) the relationship of team self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Therefore, to maintain or promote team performance, monitoring is unequivocally necessary for nurse teams during the COVID-19 pandemic. On the one hand, nurses can monitor the performance of a team to which they belong to gain insight into their team’s mishandling of work processes and correct the resulting errors; on the other hand, nurses can circumvent underperformance by self-reflecting on their own performance (i.e., self-monitoring), such as “what went well” and “what could have done better” [ 36 ]. Furthermore, previous research has found that team performance is positively associated with teamwork quality, and monitoring is an important prerequisite for effective teamwork [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to maintain or promote team performance, monitoring is unequivocally necessary for nurse teams during the COVID-19 pandemic. On the one hand, nurses can monitor the performance of a team to which they belong to gain insight into their team’s mishandling of work processes and correct the resulting errors; on the other hand, nurses can circumvent underperformance by self-reflecting on their own performance (i.e., self-monitoring), such as “what went well” and “what could have done better” [ 36 ]. Furthermore, previous research has found that team performance is positively associated with teamwork quality, and monitoring is an important prerequisite for effective teamwork [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Methodologically, the finding that the same factors may affect supervisors’ and trainees’ ratings of teamwork to different degrees suggests caution when attempting to compare or aggregate team members’ ratings of teamwork quality, even when ratings of teamwork do not differ in their numerical value ( Tscholl et al, 2015 ; Sebok-Syer et al, 2018 ). Practically, the same finding is informative for educators and practitioners who need to decide on the necessity of organizing a debriefing or after-action review ( Jarrett et al, 2016 ; Weiss et al, 2017 ) after a team event or on ways to (re)design workplace-based settings and processes; given our findings, it seems indicated to collect ratings of all participating members and not just those of the seniors or leaders (see also Hautz, S. C. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 56%
“…An important finding of research into perceived teamwork quality is that perceptions of teamwork vary with position in the organizational hierarchy ( Hautz, S. C. et al, 2020 ), seniority ( Fleming et al, 2006 ), discipline ( Ummenhofer et al, 2001 ), and professional group ( Temkin-Greener et al, 2004 ). For example, studies in health care have found that physicians consistently rate the quality of teamwork higher than nurses do ( Flin et al, 2006 ; Makary et al, 2006 ; Wauben et al, 2011 ; Tang et al, 2013 ; Müller et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, self‐monitoring could have positive impacts on patient‐level outcomes 57 and workplace clinical behaviours 58,59 . Most of the studies that measured self‐monitoring, however, focused on the accuracy of self‐judgement of performance compared with an expert rating, 22,29–32,34–36,44,45,60–71 peer rating 35,72 or standardised clinical management 37–39,47,73–75 . Studies showed everything from no agreement to strong agreement between self‐ratings and expert ratings.…”
Section: Resultsmentioning
confidence: 99%